Audio on the Internet: History and Evolution of Podcasts - Martin KUCHTA (Communications of International Proceedings, 2021)
Traditional perception of audio format positions it into radio devices, which widespread use caused creation of new mass media channel. However, similar to other media formats, also audio found an utilization on the internet, where modified forms of it became attractive to users and found a way to become a part of daily dose of media consumption. Audio format on the internet has come a long way from RSS systems to popular podcasts, which spread consumption caused its inherent part of communication and advertising strategies of most of modern brands. The main aim of the paper is to gather appropriate amount of theoretical and internet sources to develop an evolution timeline of podcasts. The final timeline consists of 21 points, which were crucial for evolution of podcasts. The timeline year range begins in the year 2000 when RSS feed was firstly used and finishes in the year 2019 when specialists have begun to be concerned about the influence of podcasts popularity and frequent consumption on position and future of traditional radio media channel.
Keywords: Audio; Podcast; Radio; Streaming Services